American Radium Society (ARS) Appropriate Use Criteria (AUC) for Extrahepatic Cholangiocarcinoma. (19th February 2023) - Tchelebi, Leila T.; Jethwa, Krishan R.; Levy, Anna T.; Anker, Christopher J.; Kennedy, Timothy; Grodstein, Elliot; Hallemeier, Christopher L.; Jabbour, Salma K.; Kim, Ed; Kumar, Rachit; Lee, Percy; Small, William; et al.
Abstract : Although uncommon, extrahepatic cholangiocarcinoma (EHCC) is a deadly malignancy, and the treatment approaches remain controversial. While surgery remains the only cure, few patients are candidates for resection up front, and there are high rates of both local and distant failure following resection. Herein, we systematically review the available evidence regarding treatment approaches for patients with EHCC, including surgery, radiation, and chemotherapy. The evidence regarding treatment outcomes was assessed using the Population, Intervention, Comparator, Outcome, and Study design (PICOS) framework. A summary of recommendations based on the available literature is outlined for specific clinical scenarios encountered by providers in the clinic to guide the management of these patients.